Lightweight skiing helmet material and preparation method thereof

Through the blending and composite fiber reinforcement of random copolymer polypropylene and block copolymer polypropylene and composite fiber reinforcement, the problems of short service life, poor cold resistance and photoaging of ski helmet materials are solved, and high-performance lightweight ski helmet materials are prepared.

CN119684715APending Publication Date: 2025-03-25MUDANJIANG NORMAL UNIV

Patent Information

Application Number
CN202411888629.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a light skiing helmet material and a preparation method thereof, and relates to the technical field of high polymer materials. The lightweight skiing helmet material provided by the invention at least comprises the following raw materials in parts by mass: 40-50 parts of polypropylene random copolymer, 40-50 parts of polypropylene block copolymer, 10-20 parts of composite fibers, 2-5 parts of polypropylene grafted maleic anhydride, 0.1-0.5 part of an antioxidant, 0.5-1 part of a lubricant and 0.1-0.5 part of a curing agent. The polypropylene random copolymer and the polypropylene block copolymer are blended, and then the composite fibers are added for reinforcement, so that the prepared lightweight skiing helmet material can be used for preparing skiing helmets which are light in weight, high in low-temperature impact strength and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a lightweight ski helmet material and a preparation method thereof. Background Art

[0002] A ski helmet is generally composed of a shell, a lining, an adjuster, a fixing device, a buckle and a goggle buckle. The main function of a helmet is to ensure the safety of the user's head in the event of an accident during skiing. On the other hand, skiing is about speed and skill, and helmets also require both lightweight and aerodynamic performance. Therefore, the weight of the ski helmet itself is also an important factor in choosing. For ski helmets of the same size, try to choose a light one. Wearing a heavy helmet for a long time will affect the quality of skiing.

[0003] The materials of helmet shells are generally divided into ABS engineering plastics, PC / ABS composite materials, fiberglass, carbon fiber, etc. The materials are required to have excellent weather resistance, wear resistance, impact resistance and compression resistance. Hard and lightweight materials are the first choice for the shell. At present, the shells of ski helmets sold on the market are mostly ABS (a kind of engineering plastics), with a density of 1.08g / cm 3 , the weight of the products is mostly above 600g, and some even weigh up to 800g. However, ABS engineering plastics are used in helmet shells, which lack strength and toughness, are easily broken during high-speed impacts, and have almost no buffering effect. In terms of impact resistance, buffering and dispersing impact force, it is still difficult to meet the protection needs of motorcycle helmets. Therefore, under the premise of ensuring the safety of athletes' heads, the development of ski helmets that are lightweight to wear, have high and low temperature impact toughness and shock absorption functions has always been the focus of the industry and research and development.

[0004] Polypropylene is made of propylene as a monomer through catalytic polymerization and granulation. Polypropylene is a crystalline polymer with a regular structure. It is a light milky white granular material, odorless, non-toxic, and lightweight thermoplastic resin. The relative density is 0.90-0.91, which is the lightest among general resins. It has good mechanical properties and good cold resistance. Therefore, it can still maintain excellent impact toughness in a long-term cold environment, play a buffering role, and protect the safety of the skier's head; the key is that compared with existing helmet materials such as ABS, it has a lower density, lower production and manufacturing costs, and better low-temperature toughness. However, if polypropylene materials are used to replace existing ABS materials to make helmets, the following problems will arise: 1. The anti-aging performance of polypropylene materials is poor, and it is very easy to cause the breakage of molecular chains under light conditions, thereby reducing mechanical properties; 2. The cold resistance of a single polypropylene material is not enough, and the low-temperature impact strength of the material needs to be improved to meet the strength requirements for preparing helmets. Summary of the invention

[0005] The purpose of the present invention is to provide a lightweight ski helmet material and a preparation method thereof, so as to solve the following technical problems: Existing polypropylene materials for ski helmets have the problems of short service life, poor cold resistance and easy light aging.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A lightweight ski helmet material and a preparation method thereof, comprising at least the following raw materials in parts by weight: 40-50 parts of random copolymer polypropylene, 40-50 parts of block copolymer polypropylene, 10-20 parts of composite fiber, 2-5 parts of polypropylene grafted maleic anhydride, 0.1-0.5 parts of antioxidant, 0.5-1 parts of lubricant and 0.1-0.5 parts of ripening agent.

[0007] As a further solution of the present invention: the composite fiber comprises at least carbon fiber and aramid fiber, and the mass ratio of the carbon fiber to the aramid fiber is 1:2-4.

[0008] As a further solution of the present invention: the preparation method of the composite fiber comprises the following steps: The carbon fiber is placed in acetone, condensed and refluxed at a temperature of 110° C., and then the carbon fiber is washed, filtered and dried with deionized water to obtain a pretreated carbon fiber; The pretreated carbon fiber is immersed in a Tris-HCl buffer solution, dopamine solution is added and mixed, and the mixture is immersed for 24-36 hours, and then filtered, washed and dried to obtain dopamine-modified carbon fiber; The aramid fiber was mixed with dimethyl sulfoxide, stirred at room temperature for 24 hours, and then the dispersion was freeze-dried at -50°C for 36-48 hours to obtain nano-aramid fiber; The nano-aramid fiber is dissolved in a dimethyl sulfoxide solution to obtain a uniform nano-aramid fiber dispersion, and the dopamine-modified carbon fiber is added to perform blending and compounding for 5-10 minutes, followed by filtering, water washing, alcohol washing and drying to obtain a composite fiber.

[0009] As a further solution of the present invention: the concentration of the dopamine solution is 0.5-2.5 g / L, and the pH of the Tris-HCl buffer solution is 8.5.

[0010] As a further solution of the present invention: the concentration of the nano-aramid fiber in the nano-aramid fiber dispersion is 0.01-0.2 wt %.

[0011] As a further solution of the present invention: the antioxidant is one of antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 626, antioxidant PEPQ or antioxidant 412S, or a mixture of several of them.

[0012] As a further solution of the present invention: the lubricant is one or a mixture of calcium stearate, EBS, and polyethylene wax.

[0013] As a further embodiment of the present invention: the curing agent is one or a mixture of tert-butyl hydroperoxide, tert-butyl peroxyacetate, azobisisobutyronitrile, azobisisoheptanenitrile, diisopropylbenzene peroxide, and di-tert-butyl diisopropylbenzene peroxide.

[0014] A method for preparing a lightweight ski helmet material as described in any one of the above, comprising at least the following preparation steps: Add random copolymer polypropylene, block copolymer polypropylene, polypropylene grafted maleic anhydride, antioxidant, and lubricant according to weight proportion into a high-speed mixer, and premix for 1-3 minutes to obtain a premix; The premix is ​​added into a twin-screw extruder through a hopper, and the composite fiber is added into the extruder through a side feeder. After meshing, plasticizing, mixing, extruding, drawing, air drying and granulation, a lightweight ski helmet material is obtained.

[0015] As a further solution of the present invention: the extrusion temperature of the extruder from feeding to the die is 120°C, 180°C, 190°C, 200°C, 210°C, 210°C, 215°C.

[0016] Beneficial effects of the present invention: The present invention uses random copolymer polypropylene and block copolymer polypropylene for blending as a base material, and then adds composite fibers for reinforcement to prepare a lightweight ski helmet material. Due to the low density of polypropylene, the weight of the obtained ski helmet is reduced. The present invention selects random copolymer polypropylene and block copolymer polypropylene for blending to improve the low-temperature impact strength of the composite material, and then adds composite fibers of carbon fiber and aramid fiber for blending reinforcement. On the one hand, the carbon fiber enhances the rigidity of the composite material while giving the material excellent impact resistance, achieving a balance between rigidity and toughness. On the other hand, the aramid fiber increases the anti-aging performance of the composite material and prolongs the service life of the material. The preparation method of the lightweight ski helmet material obtained by the present invention is simple, and a ski helmet with light weight, high low-temperature impact strength, and long service life can be prepared, which can be widely used in the preparation of ski equipment.

[0017] The present invention selects random copolymerization polypropylene and block copolymerization polypropylene to blend. In the block copolymerization polypropylene, ethylene and propylene generate elastic block segments with high impact resistance, which are uniformly block-copolymerized with the main material polypropylene, so the block copolymerization polypropylene has higher impact strength. In the present invention, the blending ratio of random copolymerization polypropylene and block copolymerization polypropylene is controlled to be 1:0.8-1.25, and the contents of random copolymerization polypropylene and block copolymerization polypropylene are equivalent to improve the normal temperature and low temperature impact resistance of the blended material. And the random copolymerization polypropylene and block copolymerization polypropylene have good compatibility, so that the flowability of the blended material in the molten state is increased, and the processing performance is also improved.

[0018] The present invention also adds composite fiber for blending, the composite fiber is nano-aramid fiber coated carbon fiber, and dopamine is used to modify the carbon fiber, so that the carbon fiber becomes a more excellent skeleton material, so that the carbon fiber is easier to combine with the aramid fiber with the same surface inertia, and more active points are provided for the surface of the carbon fiber, which greatly improves the adhesion between the carbon fiber and the resin substrate, increases its specific surface area, increases the number of active carbon atoms on the surface edge, and enhances the surface energy, thereby enhancing the interface bonding strength between the polypropylene composite matrix and the modified carbon fiber, thereby increasing the mechanical properties of the carbon fiber reinforced polypropylene composite material. In addition, the aramid fiber selected is nano-aramid fiber, which replaces the conventional para-chopped aramid fiber, so that the aramid fiber particle size becomes smaller, thereby being more conducive to the deposition of aramid fiber on the surface of the carbon fiber, and can improve the reflection, scattering and consumption of ultraviolet rays, and improve the anti-aging performance of the composite material. The composite fiber prepared by the present invention gives full play to the synergistic effect of carbon fiber and para-aramid fiber, has the characteristics of low density, high strength and high modulus, can better improve the mechanical properties and anti-aging performance of the blended material, and prolong the service life of the ski helmet material. DETAILED DESCRIPTION

[0019] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 The preparation method of the composite fiber comprises the following steps: 1.5 g of carbon fiber was placed in acetone, condensed and refluxed at a temperature of 110° C., and then the carbon fiber was washed with deionized water, filtered and dried to obtain pretreated carbon fiber; The pretreated carbon fiber is immersed in a Tris-HCl buffer solution with a pH of 8.5, 0.5 g / L dopamine solution is added and mixed, and the mixture is immersed for 24 hours, and then filtered, washed and dried to obtain dopamine-modified carbon fiber; 0.5 g of aramid fiber was mixed with 50 mL of dimethyl sulfoxide and stirred at room temperature for 24 h, and then the dispersion was freeze-dried at -50 °C for 48 h to obtain nano-aramid fiber; The nano-aramid fiber was dissolved in a dimethyl sulfoxide solution to obtain a uniform nano-aramid fiber dispersion with a concentration of 0.01 wt%, and the dopamine-modified carbon fiber was added to blend for 8 minutes, followed by filtration, water washing, alcohol washing and drying to obtain composite fibers.

[0021] Example 2 The preparation method of the composite fiber comprises the following steps: 2 g of carbon fiber was placed in acetone, condensed and refluxed at a temperature of 110° C., and then the carbon fiber was washed with deionized water, filtered and dried to obtain pretreated carbon fiber; The pretreated carbon fiber is immersed in a Tris-HCl buffer solution with a pH of 8.5, 0.5 g / L dopamine solution is added and mixed, and the mixture is immersed for 24 hours, and then filtered, washed and dried to obtain dopamine-modified carbon fiber; 0.5 g of aramid fiber was mixed with 50 mL of dimethyl sulfoxide and stirred at room temperature for 24 h, and then the dispersion was freeze-dried at -50 °C for 48 h to obtain nano-aramid fiber; The nano-aramid fiber was dissolved in a dimethyl sulfoxide solution to obtain a uniform nano-aramid fiber dispersion with a concentration of 0.01 wt%, and the dopamine-modified carbon fiber was added to blend for 8 minutes, followed by filtration, water washing, alcohol washing and drying to obtain composite fibers.

[0022] Example 3 The preparation method of a lightweight ski helmet material comprises the following steps: 40 parts by weight of random copolymer polypropylene, 45 parts by weight of block copolymer polypropylene, 3 parts by weight of polypropylene grafted maleic anhydride, 0.5 parts by weight of antioxidant 1010, 1 part by weight of lubricant calcium stearate and 0.5 parts by weight of aging agent tert-butyl hydroperoxide were added into a high-speed mixer according to their weight parts, and premixed for 1-3 minutes to obtain a premix; The premix was added into a twin-screw extruder through a hopper, and 10 parts by weight of the composite fiber prepared in Example 1 was added into the extruder through a side feeder. The extrusion temperature of the extruder was (from feeding to die) 120°C, 180°C, 190°C, 200°C, 210°C, 210°C, and 215°C. After meshing, plasticizing, mixing, extruding, drawing, air drying, and granulation, a lightweight ski helmet material was obtained.

[0023] Example 4 The preparation method of a lightweight ski helmet material comprises the following steps: 40 parts by weight of random copolymer polypropylene, 45 parts by weight of block copolymer polypropylene, 3 parts by weight of polypropylene grafted maleic anhydride, 0.5 parts by weight of antioxidant 1010, 1 part by weight of lubricant calcium stearate and 0.5 parts by weight of aging agent tert-butyl hydroperoxide were added into a high-speed mixer according to their weight parts, and premixed for 1-3 minutes to obtain a premix; The premix was added into a twin-screw extruder through a hopper, and 10 parts by weight of the composite fiber prepared in Example 2 was added into the extruder through a side feeder. The extrusion temperature of the extruder was (from feeding to die) 120°C, 180°C, 190°C, 200°C, 210°C, 210°C, and 215°C. After meshing, plasticizing, mixing, extruding, drawing, air drying, and granulation, a lightweight ski helmet material was obtained.

[0024] Example 5 The preparation method of a lightweight ski helmet material comprises the following steps: 40 parts by weight of random copolymer polypropylene, 40 parts by weight of block copolymer polypropylene, 3 parts by weight of polypropylene grafted maleic anhydride, 0.5 parts by weight of antioxidant 1010, 1 part by weight of lubricant calcium stearate and 0.5 parts by weight of aging agent tert-butyl hydroperoxide were added into a high-speed mixer according to their weight parts, and premixed for 1-3 minutes to obtain a premix; The premix was added into a twin-screw extruder through a hopper, and 15 parts by weight of the composite fiber prepared in Example 1 was added into the extruder through a side feeder. The extrusion temperature of the extruder was (from feeding to die) 120°C, 180°C, 190°C, 200°C, 210°C, 210°C, and 215°C. After meshing, plasticizing, mixing, extruding, drawing, air drying, and granulation, a lightweight ski helmet material was obtained.

[0025] Example 6 The preparation method of a lightweight ski helmet material comprises the following steps: 40 parts by weight of random copolymer polypropylene, 40 parts by weight of block copolymer polypropylene, 3 parts by weight of polypropylene grafted maleic anhydride, 0.5 parts by weight of antioxidant 1010, 1 part by weight of lubricant calcium stearate and 0.5 parts by weight of aging agent tert-butyl hydroperoxide were added into a high-speed mixer according to their weight parts, and premixed for 1-3 minutes to obtain a premix; The premix was added into a twin-screw extruder through a hopper, and 15 parts by weight of the composite fiber prepared in Example 2 was added into the extruder through a side feeder. The extrusion temperature of the extruder was (from feeding to die) 120°C, 180°C, 190°C, 200°C, 210°C, 210°C, and 215°C. After meshing, plasticizing, mixing, extruding, drawing, air drying, and granulation, a lightweight ski helmet material was obtained.

[0026] Comparative Example 1 Compared with Example 3, the step of preparing the composite fiber is omitted. In Comparative Example 1, only the composite fiber prepared in Example 1 added in Example 3 is replaced by carbon fiber. The other components and preparation method are completely consistent with Example 4.

[0027] Comparative Example 2 Compared with Example 3, the step of preparing the composite fiber is omitted. In Comparative Example 2, only the composite fiber prepared in Example 1 added in Example 3 is replaced by para-chopped aramid fiber. The other components and preparation method are completely consistent with Example 4.

[0028] Comparative Example 3 Compared with Example 3, the step of preparing the composite fiber is omitted. In Comparative Example 3, only 45 parts by mass of block copolymer polypropylene added in Example 3 is replaced by random copolymer polypropylene. The other components and preparation method are completely consistent with Example 4.

[0029] Comparative Example 4 Compared with Example 3, the step of preparing the composite fiber is omitted. In Comparative Example 4, only 40 parts by mass of random copolymer polypropylene added in Example 3 is replaced by block copolymer polypropylene. The other components and preparation method are completely the same as those of Example 4.

[0030] Performance Testing The lightweight ski helmet materials prepared in Examples 3-6 and Comparative Examples 1-4 were tested for mechanical properties according to GB / T1040 "Determination of tensile properties of plastics" and GB / T2546.2-2003 "Plastics polypropylene molding and extrusion materials Part 2: Sample preparation and performance determination"; UV aging resistance: at a wavelength of 315-400nm and a light intensity of 6000μw / cm 2 The samples were exposed to ultraviolet light for 30 days. The elongation at break retention of each group of samples after exposure for 30 days was measured according to GB / T1040 "Determination of tensile properties of plastics". The test results are shown in the table below.

[0031] It can be seen from the above table that the lightweight ski helmet materials prepared in Examples 3-6 of the present invention have good tensile properties, bending properties, low temperature resistance and aging resistance. In Comparative Example 1, carbon fiber is added instead of the composite fiber prepared in Example 1, and the obtained composite material has excellent mechanical properties but poor aging resistance. In Example 2, aramid fiber is added instead of the composite fiber prepared in Example 1, and the mechanical properties of the obtained composite material are greatly reduced. In Examples 3 and 4, random copolymer polypropylene or pure block copolymer polypropylene is used instead of the blend of two polypropylene materials, and the low temperature resistance of the obtained composite material is not improved.

[0032] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A lightweight ski helmet material, characterized in that: At least the following raw materials are included: 40-50 parts of random copolymer polypropylene, 40-50 parts of block copolymer polypropylene, 10-20 parts of composite fiber, 2-5 parts of polypropylene grafted maleic anhydride, 0.1-0.5 parts of antioxidant, 0.5-1 parts of lubricant and 0.1-0.5 parts of ripening agent.

2. A lightweight ski helmet material according to claim 1, characterized in that: The composite fiber includes at least carbon fiber and aramid fiber, and the mass ratio of the carbon fiber to the aramid fiber is 1:2-4.

3. A lightweight ski helmet material according to claim 2, characterized in that: The preparation method of the composite fiber comprises the following steps: The carbon fiber is placed in acetone, condensed and refluxed at a temperature of 110° C., and then the carbon fiber is washed, filtered and dried with deionized water to obtain a pretreated carbon fiber; The pretreated carbon fiber is immersed in a Tris-HCl buffer solution, dopamine solution is added and mixed, and the mixture is immersed for 24-36 hours, and then filtered, washed and dried to obtain dopamine-modified carbon fiber; The aramid fiber was mixed with dimethyl sulfoxide, stirred at room temperature for 24 hours, and then the dispersion was freeze-dried at -50°C for 36-48 hours to obtain nano-aramid fiber; The nano-aramid fiber is dissolved in a dimethyl sulfoxide solution to obtain a uniform nano-aramid fiber dispersion, and the dopamine-modified carbon fiber is added to perform blending and compounding for 5-10 minutes, followed by filtering, water washing, alcohol washing and drying to obtain a composite fiber.

4. A lightweight ski helmet material according to claim 3, characterized in that: The concentration of the dopamine solution is 0.5-2.5 g / L, and the pH of the Tris-HCl buffer solution is 8.

5.

5. A lightweight ski helmet material according to claim 3, characterized in that: The concentration of the nano-aramid fiber in the nano-aramid fiber dispersion is 0.01-0.2 wt %.

6. The lightweight ski helmet material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 626, antioxidant PEPQ or antioxidant 412S, or a mixture of several of them.

7. The lightweight ski helmet material according to claim 1, characterized in that: The lubricant is one of calcium stearate, EBS and polyethylene wax or a mixture of the two.

8. The lightweight ski helmet material according to claim 1, characterized in that: The curing agent is one of tert-butyl hydroperoxide, tert-butyl peroxyacetate, azobisisobutyronitrile, azobisisoheptanenitrile, diisopropylbenzene peroxide, and di-tert-butyl diisopropylbenzene peroxide, or a mixture of several of them.

9. A method for preparing a lightweight ski helmet material according to any one of claims 1 to 8, characterized in that: The method comprises at least the following preparation steps: Add random copolymer polypropylene, block copolymer polypropylene, polypropylene grafted maleic anhydride, antioxidant, and lubricant according to weight proportion into a high-speed mixer, and premix for 1-3 minutes to obtain a premix; The premix is ​​added into a twin-screw extruder through a hopper, and the composite fiber is added into the extruder through a side feeder. After meshing, plasticizing, mixing, extruding, drawing, air drying and granulation, a lightweight ski helmet material is obtained.

10. The method for preparing a lightweight ski helmet material according to claim 9, characterized in that: The extrusion temperature of the extruder from feeding to the die is 120°C, 180°C, 190°C, 200°C, 210°C, 210°C, and 215°C.

Citation Information

Patent Citations

  • Recovered carbon fiber reinforced polypropylene composite material and preparation method thereof

    CN103571036A

  • Preparation method of water dispersible aramid nanofiber and application thereof

    CN104562650A

  • Preparation method of p-aramid nanofiber

    CN105153413A

  • Composite material of modified carbon fibers and nanoaramid fibers and preparation method of composite material

    CN108610628A

  • Carbon-glass composite fiber reinforced polypropylene material and preparation method thereof

    CN109705474A

Cited By

  • A lightweight ski helmet material and its preparation method

    GB2703432A